Pineapple residue management practices and fertilizer regimes: Effects on P and K uptake, yield and some economic implications - Ahmed, Osumanu Haruna; Mohd Hanif, Ahmad Husni; Abd Rahim, Anuar; Musa, Mohamed Hanafi (Universiti Putra Malaysia Press, 2001)
The study was carried out to determine the most effective, efficient, and profitable combination of fertilizer regime and pineapple residue management practice for pineapple grown on tropical peat. Three residue management practices, namely; (i) In situ decomposition of pineapple residue without any disturbance (R1), (ii) Stacking of pineapple residue slashed and raked from 0.6 m x 10 m beds into 0.9 x 10 m beds (R2), and (iii) In situ burning of pineapple residue (RJ) were used in combination with three fertilizer regimes; (i) application of P and K at the 651h, 135th, 19151, and 233'"d days after planting (F1), (ii) application of P and K at the 651h , 135t1 ·, and 191st days after planting (F2), and (iii) application of P and K at the 65t11 , 1351 and 191'1 days after planting but sharing fertilizer amount of the 23Jrd day between the 1351h and 19151 days (F3). The effect of the three residue management practices on P and K uptake as well as fruit yield was not significant. Similar observation was made for the three fertilizer regimes. In terms of cost, R1 was the cheapest residue management practice with RJ being the most expensive practice. F2 emerged the cheapest fertilizer regime while F1 was the most expensive regime. The most cost effective treatment combination was R1F2. Burning, stacking of pineapple residue in rows or leaving pineapple residue to decompose in situ did not improve K and P uptake as well as fruit yield. The application of K (188 kg/hay and P (7 kg/hay fertilizers at 23Jrd day after planting is not necessary and lJy omitting it the practice could save as much as RM 187. 98/ha. The application of muriate of potash and China phosphate rock at the 651h, 135t1 ·, and 19151 days (F2) under in situ decomposition of pineapple residue (R1) looks promising in terms of the cost effectiveness.